2012
DOI: 10.1128/iai.00149-12
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Ligand Pretreatment Attenuates Retinal Microglial Inflammatory Response but Enhances Phagocytic Activity toward Staphylococcus aureus

Abstract: ABSTRACTStaphylococcus aureusis a leading cause of severe endophthalmitis, which often results in vision loss in some patients. Previously, we showed that Toll-like receptor 2 (TLR2) ligand pretreatment prevented the development of staphylococcal endophthalmitis in mice and suggested that microglia might be involved in this protective effect (Kuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 62 publications
1
89
0
Order By: Relevance
“…TLR2 is also important in mediating inflammation in Staphylococcus aureus endophthalmitis (Kochan et al, 2012 and Talreja et al, 2015). We do not know whether the pili of Bacillus interact with these innate immune receptors and are, in fact, TLR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 is also important in mediating inflammation in Staphylococcus aureus endophthalmitis (Kochan et al, 2012 and Talreja et al, 2015). We do not know whether the pili of Bacillus interact with these innate immune receptors and are, in fact, TLR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…As ZIKV was found to infect multiple retinal cell types and to induce the expression of multiple potential entry receptors, we next determined whether ZIKVinfected retinal cells elicit an innate immune response. TLRs have been shown to play an important role in orchestrating retinal innate responses in microbial infection (30,31,(38)(39)(40)(41), with TLR3 being implicated in viral infection. Our data showed that TLR3 mRNA expression was significantly upregulated in both ZIKVinfected Pr.…”
Section: Zikv Infects Multiple Retinal Cell Types and Induces Cell Dementioning
confidence: 99%
“…The effect of Ply187 treatment on intraocular inflammation was assessed by measuring cytokine/chemokine levels in retinal tissue lysates via an enzymelinked immunosorbent assay (ELISA) for mouse interleukin-6 (IL-6), IL-1␤, and tumor necrosis factor alpha (TNF-␣) (BD Biosciences, San Diego, CA) and macrophage inflammatory protein 2 (MIP-2) and KC (R&D Systems, Minneapolis, MN). Flow cytometry with an Accuri C6 apparatus (BD Biosciences, Ann Arbor, MI) was used to determine polymorphonuclear leukocyte (PMN) infiltration as described previously (31,32).…”
Section: Bacterial Burden Estimations the Bacterial Burdens In Both mentioning
confidence: 99%